Phosphate fertilizer for more vigorous BRS SCS Belluna banana plants results in high yield and quality in different crop cycles - Hebert Teixeira Cândido; Magali Leonel; Sarita Leonel; Paulo Ricardo Rodrigues de Jesus; Lucas Felipe dos Ouros; Edson Shigueaki Nomura; Oriel Tiago Kölln (Revista Brasileira de Ciência do Solo)
ABSTRACT Phosphorus is essential for plant metabolism. Although banana plants do not absorb large quantities, most of this mineral is exported together with the fruits, where the nutrients are related to sensory, nutritional, and technological qualities. Highly weathered soils, such as those found in most of Brazil, can immobilize phosphorus because of the cationic charges in iron and aluminum ions, making the element unavailable to plants and more challenging for phosphate fertilization. Brazil is the fourth-largest banana producer worldwide and plays an important role in national agribusiness. New banana cultivars are frequently introduced to address the adversities of banana farming and meet consumer expectations. This study aimed to evaluate the application levels of P2O5 in the BRS SCS Belluna banana plant in two crop cycles. A randomized block design with five blocks in a 6 × 2 factorial scheme was used. The first factor was the level of phosphorus application (P2O5), and the second factor was the crop cycle (first and second crop cycles). Variables related to plant vigor, production, and fruit quality were also evaluated. Shoot mass, plant height and diameter, number of photosynthetically active leaves, bunch yield, fruit mass, and nutritional aspects were analyzed. All plant biometric variables were positively affected by phosphate fertilization. Application of P2O5 promoted more vigorous banana plants with a larger number of leaves at the end of the crop cycle, and these variables were positively correlated with the production of bunches, fruit mass, and nutritional quality. The bunch yield per crop cycle increased by up to 84 % compared to the lowest level of P2O5 applied. In short, the BRS SCS Belluna banana plant responded well to phosphorus dosage, positively affecting plant vigor, which significantly influenced the production of bunches, fruit filling, and quality. The best results were achieved at P2O5 application levels close to the recommended reference level.